Electronic Parts Counting in Physics Laboratory Using Difference of Gaussians Edge Extraction - Leelawattananon, Tanaporn; Chittayasothorn, Suphamit (My University, 2024)
Small electronic parts counting in the physics laboratory is a challenging task. These small objects such as resistors, capacitors, and inductors are used in physics laboratories and because of their numbers and small size, are hard to count in a short period of time. The precise inventory of these small electronics parts is therefore compromised. In this paper we present the development of a small electronics parts counting system. The system employs object edges detection using the difference of gaussian operator. This technique is suitable for those small electronic objects which have clear boundaries. By adjusting relevant parameters sigma and threshold to suit the size of the objects, the edge images are clearly detected thus enable correct counting of the objects which leads to correct inventory of electronics parts. An alternative technique using the canny edge detector operator is also used as a comparison technique. The experimental results are precise.
Keywords: contour operator; difference of gaussians operator; edge detection; gaussian smoothing subtraction; objects counting